Detection of early embryonic mortality through ultrasound scanning in water buffaloes - AWASTHl, M K; KAVANI, F S; SIDDIQUEE, G M; DHAMI, A J; SARVAIYA, N P (The Indian Journal of Animal Reproduction, 2023)
The objective of present experiment was to detect embryonic mortality by ultrasound scanning in water buffaloes during early stages of pregnancy. The uterus of freshly bred buffaloes (n=22) not returning to estrus 23 days after service were scanned by ultrasound scanner on days 23, 25, 28 and 30 post-service. The blood samples were collected on day 23 post-breeding for estimation of plasma progesterone. The reproductive tract of these animals was palpated per-rectum for confirmation of pregnancy between 60 and 70 days post-service. The early embryonic mortality was recorded between days 23 and 25 in one animal, between days 25 and 28 in one animal and between days 30 and 60 in one animal. Thus, total 3 cases of early embryonic mortality were recorded out of 17 early pregnancies yielding overall incidence of early embryonic mortality to· be 17.64%. It may be concluded that early embryonic mortality may be detected through ultrasound scanning in water buffaloes.